(untitled) (Revista Española de Fisiología, 1993)
The regulatory properties of the divalent metal ions Mg2+, Ca2+ and Mn2+ on the activity and kinetic behaviour of rat liver microsomal cholesterol esterase were studied in vitro. Mg2+ and Ca2+ exhibited similar concentration and preincubation time-dependent increases in esterase activity, with maximal stimulation at a concentration of 2 mM. However, Mn2+ had no effect at this concentration but displayed a potent inhibitory effect at concentrations above 20 mM. Activation of cholesterol esterase by Mg2+ and Ca2+ was selective in relation to i) the changes that cations produced in the enzyme kinetic constants, and ii) the chelating agents that reversed the metal ion-induced activation. Hence, the maximum rate of cholesterol ester hydrolysis doubled in the presence of Mg2+ and activation was reversed by EDTA, whereas a significant decrease in the apparent Km for cholesterol oleate was found when Ca2+ was added and this effect was blocked by ATP and EGTA. Both cations were able to reactivate cholesterol ester hydrolase activity in metal-depleted microsomes.